Evaluation of codified elastic design spectrum models for regions of low-to-moderate seismicity. Issue 70 (March 2015) - Tsang, Hing-Ho
Abstract: Design spectrum (DS) model is typically specified in a seismic code of practice for structural design. In a region of low-to-moderate seismicity where seismic code does not exist, a DS model in a well established code of practice is usually adopted, while the suitability of such model has seldom been evaluated. In this article, the elastic DS models for reference (rock) site stipulated in six major codes of practice (AS1170.4–2007, EN1998-1:2004, GB50011–2010, IBC–2012, NBCC–2010 and NZS1170.5:2004) have been compared and scrutinized. Three cities of low-to-moderate seismicity, namely, Melbourne (Australia), Hong Kong (China) and Karlsruhe (Germany), have been selected for illustrative purposes. Particular emphasis has been put on the parameterization scheme for DS model. It is found that huge discrepancies (over 100%) exist among the models, especially at the long period range, due to differences in spectral shapes and the recommended corner periods, which would lead to undesirable effects on the use of the displacement-based seismic design approach. It is urged that the values of corner periods should be determined specifically and cautiously based on the regional seismicity pattern and local geological conditions. Highlights: The first study that scrutinizes the feature of design spectrum models in six codes. The discrepancies among the models have been highlighted, quantified and explained. Insights and recommendations have been provided for developing new DS model.